Isolation, purification, and identification of catechin from Rhizophora mucronata methanol leaf extract (Bakau Kurap) - Khalid, Syamimi Md; Rejab, Sarifah; Abdullah, Nurul Husna; Sulaiman, Roslan (ANSF Publications, 2024)
Rhizophora mucronata (Bakau Kurap) is known as ‘Red mangrove’ growth in the coastal area of Sabah. The current investigation commenced following the behaviour of proboscis monkeys in Sabah, as they consumed mangrove leaves that were believed to contribute to their high sexual activity. The R. mucronata leaf is a natural source of flavonoid. Therefore, the present study aimed to isolate, identify and purify the active compound from R. mucronata leaf from Sabah by phytochemical screening and characterization using High-Performance Liquid Chromatography (HPLC), Evaporative Light Scattering Detector-HPLC (ELSD-HPLC) and Chromatography-Mass Spectrometry/Mass Spectrometry (LCMS/MS). Young leaves of R. mucronata collected around the coastal area of Sabah were authenticated at the Sabah Forestry Department, Sandakan, Sabah with a voucher specimen, R.mucronata (Bakau Kurap); SAN 149220. The leaves were oven-dried at 40 ± 3 °C overnight, powdered and subjected to 50% Soxhlet extraction using methanol: water. The extract was filtered, rotary evaporated and freeze-dried at 4 °C to remove excess solvent. The prepared extract was characterized by its total flavonoid, steroid and saponin contents. From HPLC analysis, the fraction collected matched with the catechin standard and Fraction F4 contained the highest catechin concentration (138.12 ppm). Further purification found that RM-F11 matched the catechin standard at the same retention time (RT) 6.8. Qualitative analysis using LCMS/MS, confirmed that the compound identified was catechin. Meanwhile, in Steroidogenesis, RM-F11 showed potent activity with the value of testosterone hormone released at 230.68 ± 11.2 pg/mL. The result indicated that the components of R. mucronata leaf of Sabah had the potential as an aphrodisiac agent.